A Novel Approach to Realize Si‐Based Porous Wire‐In‐Tube Nanostructures for High‐Performance Lithium‐Ion Batteries. Issue 22 (30th April 2018) - Sadeghipari, Mehrnoosh; Mohajerzadeh, Mohammad Ala; Hajmirzaheydarali, Mohammadreza; Mashayekhi, Alireza; Mohajerzadeh, Shamsoddin
Abstract: Hollow inorganic nanostructures have drawn great attention due to their fascinating features, such as large surface area, high loading capacity, and high permeability. The formation, characterization, and application of partially and entirely hollow structure by applying a Si‐based reactive ion deposition and etching method on silicon nanowire as a template are reported. This fabrication technique is extended to a stainless steel substrate to be used as the binder‐free anode for high capacity and high rate lithium‐ion batteries. The electrochemical analyses exhibit that in addition to the high initial discharge capacity of 4125 mAh g −1 at a rate of C/16, the best performing electrode shows discharge/charge capacity of as high as 3302.14/2832.1 mAh g −1, respectively, with an excellent charge capacity retention of 96.7% over 100 cycles at a rate density of 1 C. Even at a rate of 12 C, the as‐designed structure is still able to deliver an impressive 1553 mAh g −1, which probably is attributed to fast lithium diffusion in its hollow part and high porosity of Si and alumina layer. It is proved that the change in hollowness ratio significantly affects capacity retention and average coulombic efficiency of the lithium‐ion cells. Abstract : A reactive ion deposition and etching fabrication method is developed to realize silicon‐templated partially hollow tubes of Al2 O3 as a binder free anode for high capacity and high rate lithium‐ion batteries. Wire‐in‐tube structure can effectively alleviate the structural strain and tolerate the numerous volume changes of silicon wires due to the existence of hollow space in the structure.